1999
DOI: 10.1016/s0925-4773(99)00144-6
|View full text |Cite
|
Sign up to set email alerts
|

mRNA cloning and expression studies of the quail homologue of HIF-2α

Abstract: Hypoxia inducible factors (HIF) are candidate transcriptional regulators of vascular development. Unlike HIF-1alpha - the founding member of the HIF family - which is expressed more or less ubiquitously, HIF-2alpha (also called HRF, HLF and EPAS1) is highly expressed by vascular endothelial cells and was shown to activate the transcription of endothelial cell-specific receptor tyrosine kinases (tie-2 and flk-1/VEGF receptor 2) and of vascular endothelial growth factor (VEGF). Therefore HIF-2alpha is a candidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2001
2001
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 13 publications
1
14
1
Order By: Relevance
“…Shifting from oxidative phosphorylation to the O 2 -independent glycolytic pathway is the most ancient cellular response to hypoxia, occurring even in Caenorhabditis elegans (77). Interestingly, HIF-1␣ is conserved from C. elegans to humans and HIF-2␣ only exists in more complicated vertebrates such as chicken, quail, and mammals (24,28,47). Involvement of HIF-1␣, and not HIF-2␣, in this ancient glycolytic pathway makes sense based on the fact that HIF-1␣ is evolutionarily conserved and ubiquitously expressed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Shifting from oxidative phosphorylation to the O 2 -independent glycolytic pathway is the most ancient cellular response to hypoxia, occurring even in Caenorhabditis elegans (77). Interestingly, HIF-1␣ is conserved from C. elegans to humans and HIF-2␣ only exists in more complicated vertebrates such as chicken, quail, and mammals (24,28,47). Involvement of HIF-1␣, and not HIF-2␣, in this ancient glycolytic pathway makes sense based on the fact that HIF-1␣ is evolutionarily conserved and ubiquitously expressed.…”
Section: Discussionmentioning
confidence: 99%
“…Northern blot analysis was performed according to standard protocols (36). Human DNA fragments composed of the indicated nucleotides (nt) (with section numbers of the genes from GenBank) were generated through reverse transcription-PCR and cloned into pCRII-topo vector to serve as templates for 24 primers. Subsequently, biotin-labeled ribonucleotides were synthesized with a BioArray high-yield RNA transcript labeling kit (Enzo Diagnostic, Inc.).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This might reflect their distinct expression patterns and functions. For example, HIF-1␣ is present in organisms from Caenorhabditis elegans to humans, while HIF-2␣ exists only in more complicated vertebrate species, such as chicken, quail, and mammals (9,10,20). In addition, HIF-1␣ is universally expressed while HIF-2␣ expression is more tissue restricted, even in organisms where both isoforms are expressed.…”
Section: Discussionmentioning
confidence: 99%
“…Gene targeting experiments have clearly demonstrated that HIF1␣ is required for embryonic vascularization, as major defects in early vascular de-velopment were observed in homozygous mice lacking HIF1␣ (Iyer et al, 1998, Ryan et al, 1998. EPAS1 displays a more restricted expression pattern (Flamme et al, 1997, Jain et al, 1998, Elvert et al, 1999, Favier et al, 1999 and is detected mostly in the vasculature during embryonic development. In vitro studies have shown that it can transactivate the synthesis of VEGF (Ema et al, 1997), its receptor VEGFR-2 , and the angiopoietin receptor Tie2 (Tian et al, 1997).…”
Section: Introductionmentioning
confidence: 99%